Public Health Protection Against Bioterrorism via Respiratory Pathogenic Viral and Bacterial Agents using Protective Face Masks - Brookstein, David (CommonHealth, 2021)
The widespread respiratory transmission of the Covid-19 virus has taught us the importance of face masks to mitigate both the community spread of the virus and protection of wearers by face masks. As such, there could be an extremely adverse public health possibility where respiratory pathogenic agents could be spread as a means of bioterrorism. While eventually vaccines could mitigate wide spread infection, protective face masks are an important way to immediately prevent respiratory infections from various pathogenic agents. In view of the possibility of respiratory-based bioterrorism it is critical that the public might have to adopt universal usage of face masks. The CDC recommends that all families stockpile respiratory protection as part of their personal pandemic plan because face masks should be worn by all individuals during a pandemic especially one caused by bioterrorism.